Supports and challenges in the trajectories of teacher training. The case of the Instituto Superior del Profesorado "Dr. Joaquín V. González" (CABA). (Praxis Educativa, 2025)
This article analyses the supports and challenges in teacher training trajectories at the Higher Teacher Training Institute "Dr. Joaquín V. González" (Buenos Aires City). An institutional diagnosis was carried out in 2023 using a qualitative methodology that included interviews with key institutional actors such as members of the management team, professors and members of the student centre, as well as a student survey. The aims were to describe the wide variety of institutional supports for inclusion and to analyse the supports and barriers identified by students. Among the results we found that the material conditions in which the students are going through their course of studies in Buenos Aires are a major obstacle, but that the institution already provides several supports to overcome it, although many of the students are not aware of them or do not use them.
Keywords: INITIAL TEACHER TRAINING; EDUCATIONAL TRAJECTORIES; INCLUSION; HIGHER LEVEL; HIGHER TEACHER TRAINING INSTITUTES